METODE DAKWAH MENURUT AL-QURAN - Aliasan Aliasan (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Eventhough the material or the message that will be delivered is the great one, if it is not followed by the suitable method, it will be useless. Method is the important one. The message can be refused by the receiver, even also can make the aim of the material that will be delivered unclear. Expert call it by ‘the method is message’. Therefore, the accurateness of the messenger in deciding and considering the method that will be used in delivering the message is very influencial for the success of implementing ‘Islam’ in society.